Assessing Community Knowledge and Practices Regarding Dengue Fever in an Urban Slum Area of South India: A Cross Sectional Study - Keerti S. Jogdand; Pravin N. Yerpude (Medical Research and Its Applications Vol. 8, 2024)
Dengue infection is increasingly recognized as one of the world’s emerging infectious diseases. Dengue/Dengue Hemorrhagic Fever (DHF) is an emergent disease in India. The present study was carried out with the aim of assessing knowledge regarding Dengue fever among the community in an urban slum area of Andhra Pradesh. This cross-sectional study was undertaken in an urban slum area of Urban Health Centre, Guntur, which is a field practice area of the Department of Community Medicine, Katuri Medical College and Hospital, Guntur. The present cross-sectional study was undertaken in an urban slum area of UHC, Guntur, Andhra Pradesh, India. Out of 370 respondents, 291(78.65%) knew that dengue fever is transmitted by mosquitoes. Only 38(10.27%) persons could enumerate 3 symptoms of Dengue (fever, headache and bleeding). Regarding knowledge about breeding places, only 276 (74.59%) respondents knew about breeding places of mosquitoes. Regarding the source of information on Dengue fever, 191 (51.62%) came to know about Dengue fever through television. ). In the case of personal protection against mosquito bites, 274 (74.05%) respondents were relying upon Mats/coils and 63 (17.03%) were using bed nets. Despite good awareness of dengue fever, the adoption of mosquito control methods was poor in the area. Strengthening surveillance along with health education to the community and proper training of health personnel can go a long way in control of Dengue infection.